Stable polymersomes based on ionic–zwitterionic block copolymers modified with superparamagnetic iron oxide nanoparticles for biomedical applications. Issue 27 (12th June 2015) - Kania, Gabriela; Kwolek, Urszula; Nakai, Keita; Yusa, Shin-ichi; Bednar, Jan; Wójcik, Tomasz; Chłopicki, Stefan; Skórka, Tomasz; Szuwarzyński, Michał; Szczubiałka, Krzysztof; Kepczynski, Mariusz; Nowakowska, Maria
Abstract : Novel biocompatible polymersomes with semipermeable ionic membranes were used as promising delivery systems. Abstract : Stable polymersomes with semipermeable membranes were prepared by simple mixing of two oppositely charged diblock copolymers containing zwitterionic and cationic (PMPC20 - b -PMAPTAC190 ) or anionic (PMPC20 - b -PAMPS196 ) blocks. The formation of vesicular structures in the mixed solution of the block copolymers was confirmed by direct observation using the cryo-TEM technique. Superparamagnetic iron oxide nanoparticles coated with a cationic chitosan derivative (SPION/CCh) and decorated with a fluorescent probe molecule were next incorporated into the polymersome structure. The average diameter of SPION/CCh-polymersomes estimated using cryo-TEM was about 250 nm. Surface topography of the SPION/CCh-loaded vesicles was imaged using AFM and the magnetic properties of these objects were confirmed by MFM and MRI measurements. The ability of SPION/CCh-polymersomes to affect T 2 relaxation time in MRI was evaluated based on the measurements of r 2 relaxivity. The obtained value of r 2 (573 ± 10 mM −1 s −1 ) was quite high. The cytotoxicity and intracellular uptake of the SPION/CCh-loaded vesicles into EA.hy926 cells were studied. The results indicate that the SPION/CCh-polymersomes seem to be internalized by vascular endothelium and are not cytotoxic to endothelial cells up to 1 μg Fe per mL. Therefore, it can be suggested that SPION/CCh-polymersomes could prove useful as T 2 contrast agents in the MRI of endothelium.